FOSTERING CHARACTER AND A CONDUCIVE LEARNING ENVIRONMENT THROUGH SPIRITUAL LEADERSHIP - Amalia, Tiara; Arifin, Zainal; Tamrifatus Sholihah, Vetty (Jurnal Isema : Islamic Educational Management, 2025)
This study aims to analyze the implementation and managerial implications of spiritual leadership by the principal of Al-Falah Abu Lam U Private Junior high School, Aceh Besar. This school is under the auspices of the Al-Falah Islamic Boarding School. The study used a qualitative case study approach with data collection techniques through observation, interviews, and documentation. The study results showed that (1) the spiritual leadership of the principal at Al-Falah Abu Lam U Private Junior high School significantly influences student character formation, enhance learning motivation and creating a conducive school environment. By implementing spiritual leadership, schools can produce intellectually intelligent students with high moral integrity. (2) Supporting and inhibiting factors at Al-Falah Private Junior high School are material and non-material. The inhibiting factors are limited facilities, lack of funding, or rules that the authorities still need to approve. 3) This study is limited by its primary focus on a theoretical approach in examining the implementation of spiritual leadership at Al-Falah Abu Lam U Private Junior high School, Aceh Besar. Hence, this study suggests conducting further in-depth case studies and research on spiritual leadership in diverse educational contexts including public and international schools.